Artificial Intelligence Application and Corporate Financial Distress - Li, Rensi (Economics & Management Review, 2024)
With the increasingly changeable external environment, enterprises face the threat of crisis at any time and may be in financial distress. The development of new technologies in the era of artificial intelligence (AI) provides new ideas and methods for enterprises to alleviate financial distress. We will study whether AI technology can resolve the financial distress of the enterprises, and what is the impact mechanism. Through the empirical tests of Chinese listed companies, we find that AI technology can alleviate the financial distress of enterprises by improving the resource acquisition ability and risk management ability, and the heterogeneity tests find the effect of AI technology is better when the supply chain network more dispersed, the corporate governance environment better, as well as the enterprises controlled by state-owned property rights. So enterprises should increase the research and development of AI technology application, improve corporate governance to promote the effect of AI technology greater, as well as use AI technology to provide references and advices for managers’ decision-making. We enrich the theoretical research of AI in the field of financial management, and provide new ideas for companies to alleviate financial distress in practice.